2022
DOI: 10.1155/2022/8963416
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Study on the Influence of Urban Built Environment Factors on the Social Behavior of ASD Children

Abstract: The use of urban space by vulnerable groups, especially ASD children with social anxiety, is an important part of building sustainable urban development. In this study, we focus on the play behavior of ASD children from the perspective of urban planning; then, we discussed how the urban built environmental factors affect the social behavior of ASD children. In this paper, 220 parents of ASD children were given questionnaires and 197 valid questionnaires were obtained after removing invalid ones. Stepwise regre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…The essence of play is activity, and almost all the main activities of children in daily life are related to games. Research has demonstrated that urban built environments can influence children’s activities [ 12 ]. For instance, moderate urban density is friendly to children.…”
Section: Introductionmentioning
confidence: 99%
“…The essence of play is activity, and almost all the main activities of children in daily life are related to games. Research has demonstrated that urban built environments can influence children’s activities [ 12 ]. For instance, moderate urban density is friendly to children.…”
Section: Introductionmentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%